Competency Analysis, Work Rusteristics, Work Environment, Spiritual Quotient, Organizational Commitment, Organizational Citizenship Behavior and Employee Performance - Setyowati, Ety Retno (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2021)
This research aims to prove and analyze the influence of competence,work characteristics, work environment, spiritual quotient, onorganizational commitment, organizational citizenship behavior (OCB)and employee performance in the Laboratory Installation of RSUD PatutPatuh Patju West Lombok. This study is a causal explanatory study. Asample of 38 respondents, data analysis with Partial Least Square (PLS).The results showed there was a significant positive influence on:competence to OCB and employee performance; rusteristic work towardsorganizational commitment; work environment to organizationalcommitment; organizational commitment to OCB and employeeperformance; OCB on employee performance. Gained insignificantinfluence on: competence to organizational commitment; rusteristic ofemployment against OCB and employee performance; work environmenttowards OCB and employee performance; Spiritual quotient toorganizational commitment, OCB and employee performance. Theconclusion of the results of the study is that there are seven hypothesesthat can be accepted and there are eight hypotheses that are rejected.